Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Suppose I have a $2\times 2$ matrix $M$ in implicit equation form, where $(x,y)$ is transformed to $( xOut,yOut )$: $$ ax + by = xOut, \quad cx + dy = yOut $$ Now additionally I have a line $L$, also in implicit equation form: $$ ex + fy = g $$ I want to take line $L$ and transform it into the line that results from all its points being transformed by matrix $M$. One way to do it is to parameterize (assuming $f \neq 0$) and solve equations: $$ ( x,y ) = ( x,(ex-g)/f ) $$ $$ ax + b(ex-g)/f = xOut, \quad cx + d(ex-g)/f = yOut $$ $$ (a + be/f)x - g/f = xOut,\quad (c + de/f)x - g/f = yOut $$ $$ (c+de/f)xOut - (a+be/f)yOut = (-(c+de/f)g/f - (a+be/f)g/f) $$ That gives me the new line equation, which is good, but there is that pesky $f$ in the denominator. A line that is just $x = c$ should be just as valid after a transform. Of course I could go through the whole process again with the requirement that $e \neq 0$ instead, but that seems wasteful. Is there a more direct way of combining these three equations without parameterizing? They are all linear but I can't see how to put them all together in one matrix, where the output of one system is the input of another system.

share|improve this question
    
Can you format your post using the TeX commands for all the math? Otherwise, it's hard to read. –  JohnD Jan 8 '13 at 23:24
    
Yeah I know. I wish it would just format simple equations... –  Dan Jan 8 '13 at 23:26
    
Cheers to whoever just centered and italicized the equations. –  Dan Jan 8 '13 at 23:49

1 Answer 1

You will not necessarily get a new line by acting $M$ on $L$. Consider for example the zero matrix $M=O_{2\times 2}$.

Let the line $L=\{x\in{\Bbb R}^2:a\cdot x=c\}$ , where $0\neq a\in{\Bbb R}^2$ and $c\in{\Bbb R}$ are constants. Then the image of $L$ under $M$ (the output) is $$ M(L)=\{Mx:a\cdot x=c,x\in{\Bbb R}^2\}. $$ If $M$ is invertible, $M(L)=\{y\in{\Bbb R}^2:a\cdot(M^{-1}y)=c\}.$

If $M$ is not invertible, you get $M(L)=\{M(x_0+kv):k\in{\Bbb R}\}$ where $x_0$ is a point on $L$ and $v$ is such that $a\cdot v=0$. Let $(x_1',x_2')^T=Mx_0+kMv$ and cancel out $k$, you would get the equation for your new line (or a point only).

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.